Pilot testing Fostering Open eXpression among Youth (FOXY), an arts-based HIV/STI prevention approach for adolescent women in the Northwest Territories, Canada - Lys, Candice L; Logie, Carmen; Okumu, Moses (International Journal of STD & AIDS, 2018)
Fostering Open eXpression among Youth (FOXY) is an arts-based HIV prevention program developed by Northern Canadians to address sexual health, HIV, sexually transmitted infections (STIs), sexuality, and healthy relationships among Northern and Indigenous youth in Canada. We conducted a pilot study with Indigenous and Northern young women aged 13-17 years from 17 communities in the Northwest Territories to evaluate whether, in comparison to pre-intervention, FOXY participants demonstrated increased knowledge of STIs, increased safer sex self-efficacy, and increased resilience. Wilcoxon test results indicated significant increases in STI knowledge scores and safer sex self-efficacy scores. Findings suggest that FOXY holds promise as an effective method of delivering sexual health information through peer education, and increasing STI knowledge, safe sex self-efficacy, and resilience. The authors received financial support from the Canadian Institutes of Health Research and the Public Health Agency of Canada for the research of this article. CM was also supported by an Ontario Ministry of Research & Innovation Early Researcher Award.